Primeros coqueteos entre reportaje y novela: Daniel Defoe, Edgar Allan Poe y Fiodor Dostoievski - Mora Do Campo, María del Mar (Estudios sobre el Mensaje Periodístico, 2002)
Far from intending to fix a border between journalism and literature, we position ourselves in a place of common waters where a short of jobs that are more and more numerous should have room. They are texts that coincide thematically with the demands of journalism, but they differ from the traditional style norms. In spite of the fact that Tom Wolfe insisted on taking this idea (he named it “New Journalism”), as early as the eighteenth and nineteenth century some important examples of reports that added typical techniques of the novel appeared. This article studies the application of narrative techniques in those first reports and it defends them like useful or even necessary for the journalist work.